KETERSEDIAAN SARANA PRASARANA PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN DI SDN 104204 SAMBIREJO TIMUR - Suyono; Ros Suryaningsih Ge’e; Aviva Hanum Siregar; Sabina Khairunnisa (STKIP Subang, 2024)
Facilities and infrastructure are very important in supporting the success of the learning process. This research aims to determine the physical Sports physical Education and health infrastructure at SDN 104204 Sambirejo Timur. This research is qualitative with a survey method. Source of data that will be obtained by the entire population at SDN 104204 Sambirejo Timur which explains the numbers. physical education facilities and infrastructure. Data collection techniques using documentation and observation sheets, data analysis using qualitative analysis. The research results obtained by researchers regarding the number of tools used were 61 tools, with a total of 51 tools that were still good and a total of 10 tools that were damaged with the final percentage of tools that were still good being 84% and included in the very good category.